Endothelial dysfunction and the role of hypertension in Nepalese subjects with major coronary risk factors - Gautam, Mani Prasad; Gautam, Samir; Ghimire, Usha; Guruprasad, Sogunuru; Bhattacharya, Rabin; Subramanyam, Gangapatnam (Nepalese Heart Journal, 2016)
Background and Aims: Hypertension is one of the major coronary heart disease risk factors. Endothelial dysfunction is thought to be the preclinical vascular changes in the pathogenesis of atherosclerosis and it its major manifestation; coronary heart disease. This study was designed to assess the endothelial function in subjects with major coronary risk factors including hypertension. Methods: The study was conducted in a tertiary referral centre in Central Nepal. A cross-sectional study was conducted on the cohort of 100 subjects with at least one out of six major coronary heart disease risk factors. JNC 7 criteria were used to define hypertension. Brachial artery flow-mediated dilation was measured using high-resolution ultrasound. Endothelial dysfunction was defined as flow-mediated dilation value <9.99%. The association between endothelial dysfunction and hypertension was assessed by univariate and multivariate analysis. Results: Out of 100 subjects with coronary risk factors (mean age 46.75±9.95 years, mean number of risk factors 2.81± 1.17), 65% subjects were hypertensive and 35% were non-hypertensive. Hypertension as a risk factor was evident in 80.39% and 48.98% subjects with abnormal and normal endothelial response respectively (p = 0.001). In addition, 63.08% and 28.57% subjects with and without hypertension had endothelial dysfunction respectively (p=0.01). Hypertension was the only coronary risk factor associated with endothelial dysfunction in a multivariate model (p=0.04). Conclusion: Hypertension was strongly associated with endothelial dysfunction and it could be the best predictor of endothelial dysfunction and subsequent coronary heart disease in coronary heart diseases risk factor cohorts. Nepalese Heart Journal 2016; 13(1): 13-18